FILMAR-SE E VER-SE AO ESPELHO: A AUTO-REPRESENTAÇÃO DE DOCUMENTARISTAS PORTUGUESAS E BRASILEIRAS - Dra. Ana Catarina PEREIRA (Fonseca, Journal of Communication, 2023)
Self-writing has been constituted as an exercise in self-analysis and representation of many women, especially in the artistic field and, particularly, in the cinematographic one. Focusing on the cinema in Portuguese, it is easy to find a small number of women who have had the opportunity of directing fiction films, which is opposed to a greater number of filmmakers directing documentaries Among these, are being more noticed the ones who reviewed, successfully and awarded in different international film festivals, the images of the family, on both sides of the Atlantic, in two Portuguese-speaking countries.